L'apprentissage socioémotionnel à l'école primaire : compétences attendues des enseignants et formation initiale - Claire Beaumont; Natalia Garcia (Nantes Université, 2020)
This article analyses how socio-emotional learning (SEL) is taken into consideration in expected professional competences in teaching as well as in preschool/elementary teachers' initial training. Data come from the Teacher training - Orientations, professional competencies frame of reference (Quebec Government, 2001) and the websites of nine francophone universities offering a baccalaureate in preschool/elementary teaching. Results points to a certain adequacy between expectations and class curriculum in initial training particularly regarding the fragmented presence of competencies linked to SEL, with the small representation of the interpersonal dimension (self-consciousness and self-management of emotions/behaviour) as much for students as for teachers. Initial training seems to vary from one university to the other although no establishment offers a class aiming specifically at the accreditation in the teaching of these competences to students or for school staff to develop them for themselves. Representing a global educational perspective that could help school to fulfill its mission of socialization as well as promote teachers' well-being, conclusions suggest that SEL should be promoted more explicitly and systematically in schools, but that future teachers should first be trained towards it.